Calculation of the Hall Coefficient in Doped Semiconductor Superlattices with a Perpendicular Magnetic Field under the Influence of a Laser Radiation - Hoi, Bui Dinh; Trang, Pham Thi; Bau, Nguyen Quang (VNU Journal of Science: Mathematics - Physics; Vol 29 No 1, 2013)
Abstract: We consider a model of the Hall effect when a doped semiconductor superlattice (DSSL) with a periodical superlattice potential in the z -direction is subjected to a crossed dc electric field (EF)  and magnetic field , in the presence of a laser radiation characterized by electric field  (where  and  are the amplitude and the frequency of the laser radiation, respectively). By using the quantum kinetic equation for electrons and considering the electron - optical phonon interaction, we obtain analytical expressions for the Hall conductivity as well as the Hall coefficient (HC) with a dependence on B , , , , the temperature T of the system and the characteristic parameters of DSSL. The analytical results are computationally evaluated and graphically plotted for the GaAs:Si/GaAs:Be DSSL. Numerical results show the saturation of the HC as the magnetic field or the laser radiation frequency increases. This behavior is similar to the case of low temperature in two-dimensional electron systems. Keywords:   Hall effect, Quantum kinetic equation, Doped superlattices, Parabolic quantum wells, Electron - phonon interaction.